Further evidence for the East Coast fault system and faults associated with the Summerville restraining bend and their possible relationship to the 1886 Charleston, South Carolina, earthquake, USA - Marple, Ronald T.; Hurd Jr., James D. (Atlantic Geoscience)

(untitled) (Atlantic Geoscience Society, 2022)
The integration of aeromagnetic, LiDAR, and previously acquired seismic-reflection data and surficial geologic maps supports the existence of the East Coast fault system ( and faults associated with its 12⁰ Summerville restraining bend beneath the South Carolina Coastal Plain. Aeromagnetic data revealed a 10- to 15-km-wide zone of subtle, 22- to 35-km-long linear magnetic anomalies trending ~N10°E across the southern meizoseismal area of the 1886 Charleston earthquake that we postulate are associated with Cenozoic low-displacement brittle faults in the crystalline basement west of Charleston. We hypothesize that lineaments ML4 and ML5 represent the principal displacement zone along the southern end of the ECFS because they coincide with steeply dipping, west-side-up buried faults interpreted from previously acquired seismic-reflection profiles and a ~320-m dextral offset in the Brownsville Pleistocene beach ridge deposit. The alignment of the NNE-SSW-oriented Edisto dome, uplift along releveling line 9, gently upwarped longitudinal profiles along the Caw Caw and Horse Savanna swamps, local incision along the Ashley River, and exposures of the early Oligocene Ashley Formation near the incised part of the Ashley River support Quaternary uplift along the southern ECFS. The 12⁰ change in trend formed by lineaments ML4 and ML5 supports the existence of the Summerville restraining bend in the ECFS, east of which are numerous ENE-WSW- to NW-SE-oriented LiDAR lineaments that we postulate are surface expressions of faults that formed to compensate for the increased compression produced by dextral motion along the bend. Sinistral displacement along one of these proposed faults associated with the ~40-km-long, east-west-oriented Deer Park lineament may have produced the main shock of the 1886 Charleston earthquake.